Mechanical design of the magnet mirror structure for testing Nb3Sn sextupole coil of 45 GHz ECRIS. (December 2020) - Zhu, L.; Wu, W.; Yu, S.R.; Sun, L.T.; Chen, Y.Y.; Mei, E.M.; Ni, D.S.; Du, Z.Y.
Highlights: The Nb3 Sn sextupole testing coil is fabricated with a round wire. A mirror structure based on a key and bladder technology. Describes the mechanical analyses performed to estimate the sextupole's preload. The stress analysis from assembly to excitation is carried out. Strain gauge measurements have been compared with the simulation results. Abstract: The new Nb3 Sn superconducting magnet system for the fourth-generation 45 GHz ECR source is under development at the Institute of Modern Physics (IMP). A mirror structure of the Nb3 Sn sextupole testing coil based on an aluminum shell-based structure and bladder & key technology is used for studying the coil's mechanical, thermal and quench performance under realistic conditions. This paper describes the mechanical analyses performed to estimate the sextupole's preload. Based on the three-dimensional finite-element mechanical model, the stress analysis for the process of assembly, cooling down, and charging is carried out. The assembly and strain measurement results of sextupole mirror structure are also introduced in this paper.